Extracts from the Hungarian and international scientific results in Limousin cattle - Vertséné Zándoki, Rita; Kosztolányiné Szentléleki, Andrea; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
Authors introduce Hungarian and international results concerning the heritabilities of different production traits in Limousin cattle. In different experiments at different places often variant results were obtained which imply that breeders’ decisions shall rather be based on heritability values calculated for own or very similar herd. In the second part of the essay, the latest international results in Limousin breed are surveyed. Researchers take efforts to support genomic selection and to examine geotype x environment interactions. Results of experiments analyzing production traits and breed comparisons suggest that Limousin is among the top beef cattle breeds. Researches also confirm the necessarity of considering results obtained in the theme of ethology, and application of these results in selection and breeding practice.